The novel HLA‐B*39:93 allele was identified by sequence‐based typing in a French family. Issue 2 (February 2015) - Elsermans, V.; Top, I.; Farchi, O.; Varlet, P.; Labalette, M.
<x xml:space="preserve">Abstract</x> A novel HLA‐B allele, B*39:93, was identified in a French family.